2021
DOI: 10.1186/s40780-021-00212-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of osmolality on gastrointestinal fluid volume and drug absorption: potential impact on oral salt supplementation

Abstract: Background The syndrome of inappropriate secretion of antidiuretic hormone (SIADH) is the most frequent cause of hyponatremia in patients with cerebrovascular disease, and is often treated with oral salt tablets. However, we have shown that osmolality-dependent variations in gastrointestinal (GI) fluid volume can alter the concentration of a poorly permeable drug in the GI tract, potentially affecting its absorption. Here, we examined the effect of ingestion of hyperosmotic solution (10% NaCl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In this context, we have proposed that osmolality-dependent changes in GI fluid volume may indirectly affect the drug absorption process by altering the drug concentration in the GI tract. [12][13][14] Indeed, we showed that this effect could account for the AJ-atenolol interaction. Specifically, ingestion of AJ leads to fluid secretion into the GI lumen due to the high osmolality of AJ, resulting in a reduction of GI absorption of atenolol owing to its reduced concentration in the GI fluid.…”
Section: Introductionmentioning
confidence: 64%
“…In this context, we have proposed that osmolality-dependent changes in GI fluid volume may indirectly affect the drug absorption process by altering the drug concentration in the GI tract. [12][13][14] Indeed, we showed that this effect could account for the AJ-atenolol interaction. Specifically, ingestion of AJ leads to fluid secretion into the GI lumen due to the high osmolality of AJ, resulting in a reduction of GI absorption of atenolol owing to its reduced concentration in the GI fluid.…”
Section: Introductionmentioning
confidence: 64%
“…Indeed, dynamic variations in fluid volumes along the GI tract have been observed by means of fluid-sensitive MRI and PET analyses in healthy volunteers and/or experimental animals 6 , 11 . Furthermore, our recent studies have shown that the solution osmolality influences the GI fluid volume 1 5 . We also demonstrated that osmolality-dependent variations in GI fluid volume can alter drug concentration in the GI tract, and consequently change drug absorption characteristics 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Fluid volume is a major factor directly determining GI drug concentration and the amount of dissolution of poorly soluble drugs in the GI tract. We recently reported that changes in the GI fluid volume may indirectly influence the drug absorption profile by altering the drug concentration and absorption kinetics 1 5 . Furthermore, we and other research groups demonstrated that water secretion and drug resultant dilution of drug concentration in the GI tract may contribute to beverage-drug interactions that result in decreased drug absorption 1 , 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%